2002
DOI: 10.1515/znc-2002-11-1224
|View full text |Cite
|
Sign up to set email alerts
|

Notes: Flavonols from Scurrula ferruginea Danser (Loranthaceae)

Abstract: Three natural flavonols compounds have been isolated from the ethyl acetate fraction of Scurrula ferruginea Danser (Loranthaceae). Besides quercetin and quercitrin, an unusual flavonol glycoside 4″-O-acetylquercitrin was isolated. Structures were determined using spectroscopic methods including UV, NMR and HRMS-EI. The incidence of 4″-O-acetylquercitrin, not previously reported in the Loranthaceae, is discussed. Cytotoxic evaluation on four human cancer cell lines showed quercetin to be the most active with IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Despite its application as traditional medicine, there was a limited study investigated its application directly to a specific disease. Previous studies reported the potent therapeutic applications of S. ferruginea on its antioxidant activity ( Marvibaigi et al, 2014), blood pressure reduction activity (Ameer et al, 2009), and cytotoxic activity (Lohézic- Le Dévéhat et al, 2002b). However, the details about bioactive compounds related to those therapeutic effects were not mentioned in detailed from the studies.…”
Section: Conclusion and Future Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its application as traditional medicine, there was a limited study investigated its application directly to a specific disease. Previous studies reported the potent therapeutic applications of S. ferruginea on its antioxidant activity ( Marvibaigi et al, 2014), blood pressure reduction activity (Ameer et al, 2009), and cytotoxic activity (Lohézic- Le Dévéhat et al, 2002b). However, the details about bioactive compounds related to those therapeutic effects were not mentioned in detailed from the studies.…”
Section: Conclusion and Future Opportunitiesmentioning
confidence: 99%
“…The study on the potential of S. ferruginea mistletoe to inhibit cancer cell has been done by F. Lohézic- Le Dévéhat, S. Tomasi, D. Fontanel, and J. Boustie (2002a) One of the assorted mistletoes that have been common used in herbal medicine is the family of Loranthaceae. Even though there is a slightly published paper of S. ferruginea supporting a lowering activity of blood pressure (Ameer et al 2009;Marvibaigi et al 2016), within other Loranthaceae family which related species have been many reported for their activity of antihypertensive.…”
Section: B Cytotoxic Activity On Cancer Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Devehat et al [27], the peaks in the IR spectra (3350, 2926, and 1634) obtained from the leaf samples of D. falcata revealed the presence of quercitrin, which is reported as a taxonomic marker of the Loranthaceae family. The reported chemical examination of D. falcata growing on Terminalia tmentosa has revealed the presence of gallic, ellagic, and chebulinic acids, and quercetin [29].…”
Section: Antioxidative Propertiesmentioning
confidence: 99%
“…The LC 50 values for the radical scavenging activity of D. falcata from R. mucronata was 47 μg/mL and from A. lebbeck-41 µg/mL (Table 3). Önay Uçar et al [26] hydrogen donation at the C 3 position that enhanced the antioxidant activity [27].…”
Section: Antioxidative Propertiesmentioning
confidence: 99%